please answer
math
class9
Attachments:
![](https://hi-static.z-dn.net/files/dfa/6a4f76f5e04e5acbdf7098fe45cb194a.jpg)
Answers
Answered by
0
Step-by-step explanation:
(√3+1)/(√3-1)
= (√3+1)/(√3-1) × (√3+1)/(√3+1)
= {(√3+1)(√3+1)}/{(√3-1)(√3+1)}
= {(√3+1)²}/{(√3)²-(1)²}
= {3+2√3+1}/{3-1}
= (4+2√3)/2
= 2+1√3
Hence, a = 2 and b = 1
Answered by
0
Hope this will help you
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d77/b097d6861c7d370ff558e3e35dcecb82.jpeg)
Similar questions